PREVALENSI PENDERITA KATARAK DENGAN DIABETES MELITUS DI RS SRIWIJAYA PALEMBANG TAHUN 2019 - Gusmana, Danti Iwan; Erna, Riani; Handayani, Dwi (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Abstract Prevalence Of Cataract Patients With Diabetes Mellitus In Sriwijaya Palembang Hospital 2019.Cataracts are opacities that occurs in the eye lens and thus block light entering the eye. Indonesia's population has a tendency to suffer cataracts 15 years sooner than the population in the subtropics. Approximately 16-22% of cataract surgery patients under 55 years old. Patients with diabetes mellitus 4.9 times higher risk of developing cataracts. Data from the Ministry of Health in 2014 said that the prevalence of cataract in the province of South Sumatra in 2013 was recorded at 1.7%. Research shows 31.4% of cataract patients with diabetes mellitus. This study aimed to determine the prevalence of cataract patients with diabetes mellitus in hospital Sriwijaya Palembang in 2019.This research is a descriptive survey method. The study population was all patients with cataract were hospitalized in the Hospital Eye Clinic Sriwijaya many as 494 and as many as 101 used as a sample with a total sampling technique. Observed data from medical records of patients in hospital medical record Installation Sriwijaya period of January - September 2019.The results showed that cataract patients with diabetes mellitus, the most suffered by women were 60 (60.4%), age group 56-65 years (39.6%), history of diabetic retinopathy NPDR types of 7 people (6.9% ), the type of PDR of 4 people (4.0%), postoperative visual acuity of cataract with good category 57 (56.4%), while 20 (19.8%), and worse 24 (23.8%). The prevalence of cataract patients with diabetes mellitus in hospital Sriwijaya Palembang in 2019 amounted to 20.44%.